KARAKTERISTIK PERUSAHAAN TERHADAP KUALITAS IMPLEMENTASI CORPORATE GOVERNANCE - Asrudin Hormati (University of Merdeka Malang, 2009)
This study aimed to provide empirical evidence that investment opportunities,ownership concentration, leverage, firm size and quality of external audit influenced the qualityof corporate governance. The study also observed companies that listing in BEI and participatinga survey which was conducted by IICG. The observation period range was 2006-2008. Thesample selection was using purposive sampling method. The companies matched the criteriawere 53 companies, and the analysis method used was multiple regression. The results of thestudy showed that investment opportunities, ownership concentration, and leverage did notinfluence the quality of corporate governance whereas the firm size and the quality of externalaudit influenced the quality of corporate governance.